-2e+4=-5

Simple and best practice solution for -2e+4=-5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2e+4=-5 equation:



-2e+4=-5
We move all terms to the left:
-2e+4-(-5)=0
We add all the numbers together, and all the variables
-2e+9=0
We move all terms containing e to the left, all other terms to the right
-2e=-9
e=-9/-2
e=4+1/2

See similar equations:

| 7x+4x-51=34-6x | | F(n)=2n-8 | | 3(x+25)-2(-x+10)=-25 | | 2(3x-4)=-2x | | -6(7-2p)=-138 | | 10-43=39+7(x-10) | | 5x+32=7x-12 | | |7x+5|+7=65 | | 2(3x-7)=10-8 | | 7(4+3p)+8=141 | | 3x-10+x+4+2x+4=180 | | 7x+5=72 | | 5x²+37x+54=0 | | 6/b=3/5 | | 5x²-37x+54=0 | | 5(5x+6)=25+30 | | 84=w6 | | (2a-2)=2(3a-3) | | 2s–12+2s=4s–12 | | 5-2x=8-4x | | 2x^2+8x-5=8 | | 0=n^2-19/3n+2 | | x2−3x−18=10 | | 5=3f+2 | | 18-(3x-5)=5(x-1)-6 | | 2w+2(3w-5)=82 | | 4=-7x+8x | | X/3-2x+1/2=5/6 | | (2x+1)^2-(-x+1)^2=(x-1)(3x+2) | | -7p+8p=7 | | 0.02(y-9)+0.18y=0.14y-0.03(10) | | 48-3x=-109-8x |

Equations solver categories